2023
DOI: 10.3233/wor-211147
|View full text |Cite
|
Sign up to set email alerts
|

Workplace barriers among people with rheumatic and chronic back pain: Results from the work experience survey for rheumatic conditions

Abstract: BACKGROUND: The Work Experience Survey for Rheumatic Conditions (WES-RC) is a prominent feature of an evidence-based intervention to prevent premature job loss among people with arthritis. The WES-RC is used to identify client perceived barriers related to work performance. The degree to which people with arthritis and rheumatic conditions report barriers on the WES-RC has not been reported. OBJECTIVE: The purpose of this study was to characterize the barriers reported on the WES-RC. METHODS: Data from partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Workplace barriers experienced by RMD participants (n = 143) in the WORK-IT trial (Keysor et al, 2018) have also been reported (AlHeresh et al, 2023). Participants were predominantly diagnosed with osteoarthritis (43%), RA (23%), chronic back pain (13%), fibromyalgia (11%), and other RMDs.…”
Section: Updating the Wes-rc Manual And Workwell Solutions Manualmentioning
confidence: 86%
See 2 more Smart Citations
“…Workplace barriers experienced by RMD participants (n = 143) in the WORK-IT trial (Keysor et al, 2018) have also been reported (AlHeresh et al, 2023). Participants were predominantly diagnosed with osteoarthritis (43%), RA (23%), chronic back pain (13%), fibromyalgia (11%), and other RMDs.…”
Section: Updating the Wes-rc Manual And Workwell Solutions Manualmentioning
confidence: 86%
“…It is a semi‐structured interview schedule which can be conducted anywhere, either in‐person or by telephone/videocall, by healthcare professionals (HCPs) and occupational health personnel (OHP). The WES‐RC includes demographic, health, and job‐related information, as well as listing 120 potential workplace difficulties (AlHeresh et al., 2023 ; Allaire & Keysor, 2009 ). The final section of the WES‐RC consists of jointly planning with the client an individualised job retention vocational rehabilitation (JRVR) programme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation